The Impact of Social Determinants of Health in Pediatric Shunted Hydrocephalus. Issue 5 (7th May 2023) - Khalid, Syed I.; Hunter, Brittany M.; Shah, Pal; Patel, Aashka; Thomson, Kyle B.; LoPresti, Melissa A.; Roblin, Douglas W.; Lam, Sandi; Mehta, Ankit I.
Abstract : BACKGROUND: Social risk factors have been shown to negatively affect health outcomes in children. However, this has not been characterized regarding pediatric shunted hydrocephalus. OBJECTIVE: To explore the impact of social risk factors on outcomes in pediatric shunted hydrocephalus with the goal of identifying specific areas of intervention that might improve the outcomes of children undergoing cerebrospinal fluid (CSF) diversion. METHODS: In an all-payer administrative database, records between January 2010 and October 2020 were analyzed to identify children undergoing CSF shunting procedures. Children with social risk factors were compared with those without regarding rates of infection, shunt-related interventions, and mortality within 5 years of their shunting procedure. RESULTS: Among the 5420 children who underwent first-time shunting procedures, 263 (4.9%) were identified to have social risk factors. Children with identified social risk factors had increased odds of central nervous system infection (odds ratio [OR] 2.06, 95% CI 1.45-2.91), revision (OR 2.43, 95% I 1.89-3.12), and mortality (OR 2.86, 95% CI 1.23-5.72). The mean numbers of computed tomography studies (14.60 ± 17.78 vs 6.34 ± 6.10), MRI studies (18.76 ± 24.37 vs 7.88 ± 24.37), and shunt series X-rays (17.22 ± 19.04 vs 7.66 ± 8.54) were increased among children with social risk factors. CONCLUSION: Children with social risk factors had increased rates of central nervous system infection, shunt-related interventions, and mortality within 5 years of CSF shunting. We underscore the importance of characterizing the impact of social risk factors in specific conditions, such as pediatric shunted hydrocephalus, and look to future directions aimed to mitigate these risk factors with coordination and direction of individualized resources, encouragement of advocacy, and community partnership. Abstract :